2015
DOI: 10.1016/j.neuroscience.2015.01.064
|View full text |Cite
|
Sign up to set email alerts
|

Catechol-O-methyltransferase inhibition alters pain and anxiety-related volitional behaviors through activation of β-adrenergic receptors in the rat

Abstract: Reduced catechol-O-methyltransferase (COMT) activity resulting from genetic variation or pharmacological depletion results in enhanced pain perception in humans and nociceptive behaviors in animals. Using phasic mechanical and thermal reflex tests (e.g. von Frey, Hargreaves), recent studies show that acute COMT-dependent pain in rats is mediated by β-adrenergic receptors (βARs). In order to more closely mimic the characteristics of human chronic pain conditions associated with prolonged reductions in COMT, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 72 publications
(101 reference statements)
5
13
0
Order By: Relevance
“…Patients with FPS have increased levels of the catecholamines epinephrine and norepinephrine (Bote et al, 2014; Evaskus and Laskin, 1972; Perry et al, 1989; Torpy et al, 2000) alongside decreased levels of catechol-O-methyltransferase (COMT) (Marbach and Levitt, 1976; Smith et al, 2014), a ubiuitously expressed enzyme that metabolizes catecholamines (Mannisto and Kaakkola, 1999). Consistent with clinical findings, rodents receiving sustained delivery of the COMT inhibitor OR486 exhibit heightened mechanical sensitivity at multiple body sites, including the hindpaw and the abdomen (Ciszek et al, 2016; Kline et al, 2015). The development of this COMT-dependent functional pain is mediated by stimulation of peripheral β 2 - and β 3 -adrenergic receptors (β 2 - and β 3 ARs) (Ciszek et al, 2016).…”
Section: Introductionsupporting
confidence: 63%
“…Patients with FPS have increased levels of the catecholamines epinephrine and norepinephrine (Bote et al, 2014; Evaskus and Laskin, 1972; Perry et al, 1989; Torpy et al, 2000) alongside decreased levels of catechol-O-methyltransferase (COMT) (Marbach and Levitt, 1976; Smith et al, 2014), a ubiuitously expressed enzyme that metabolizes catecholamines (Mannisto and Kaakkola, 1999). Consistent with clinical findings, rodents receiving sustained delivery of the COMT inhibitor OR486 exhibit heightened mechanical sensitivity at multiple body sites, including the hindpaw and the abdomen (Ciszek et al, 2016; Kline et al, 2015). The development of this COMT-dependent functional pain is mediated by stimulation of peripheral β 2 - and β 3 -adrenergic receptors (β 2 - and β 3 ARs) (Ciszek et al, 2016).…”
Section: Introductionsupporting
confidence: 63%
“…The ‘low COMT activity’ variants are associated with increased fibromyalgia 7377 and temporomandibular disorder 78 onset and increased pain in response to experimental stimuli 78,79 and stressful events 71,80,81 . Consistent with clinical syndromes, in rodents sustained delivery of the COMT inhibitor OR486 results in pain at multiple body sites that persists for weeks and altered pain- and anxiety-related volitional behaviors 68,8284 . Persistent COMT-dependent pain is initiated by peripheral β 2 - and β 3 -adrenergic receptors (β 2 - and β 3 ARs) through release of nitric oxide, TNFα, IL-1β, IL-6, and CCL2 in plasma and maintained by increased TNF in central tissues 68,8486 .…”
Section: Neuroinflammation In Chronic Overlapping Pain Conditions Andmentioning
confidence: 82%
“…The open field test measures general locomotor activity and willingness to explore; both relate to anxiety levels [ 26 ], spontaneous discomfort or pain-like behavior [ 27 ]. We found that the total distance traveled and the percent distance traveled in the midfield were significantly reduced in NCI rats following a nutrient meal ingestion to satiety versus those in control rats, suggesting that exposure to robust neonatal colon inflammation induces postprandial anxiety-like and aversive behaviors in later life.…”
Section: Discussionmentioning
confidence: 99%